Recombination mediates production of an extrachromosomal circular DNA containing a transposon-like human element, THE-1. - Misra, R (1989)
An abundant class of HeLa extrachromosomal circular DNA containing the transposon-like element, THE-1, is shown to arise via site specific recombination. The chromosomal locus from which these circles are derived, however, is single-copy. Northern blot analysis detects homology to two polyadenylated RNAs in HeLa cells. The possible presence of an origin of replication and its role in generating these small polydisperse circles is discussed.